RESEÑA de: Alvarado Planas, Javier; Montes Salguero, Jorge; Pérez Marcos, Regina; Sánchez González, M.ª Dolores. Culturaeuropea en España . Madrid : Editorial Sanz y Torres , 2010. - Muñoz Catalán, Elisa (Revista de Derecho de la UNED (RDUNED), 2013)
-